Uji Organoleptik Es Krim Bekatul Beras Putih DenganPenambahan Ekstrak Wortel Sebagai Pewarna Alami - Sulistiyaningsih, Ika Putri; , Dra. Suparti M.Si (2016)
Rice bran has a content of , among others, proteins, minerals , fats , antioxidants , vitamin E , vitamin B complex . Carrots contain beta-carotene is quite high compared to other vegetable . Ice cream is a dairy product made by a process of freezing and agitation ( stirring ) . This study uses a completely randomized design ( CRD ) using 2 factors . Ice cream is a dairy product made by a process of freezing and agitation ( stirring ) . This study uses a completely randomized design ( CRD ) using 2 factors . In this study received power mengpunyai best on ice cream p5 treatment with a percentage of 2.75 %